TIPOLOGI MADRASAH IBTIDAIYAH BERBASIS PESANTREN PERSPEKTIF PERUBAHAN SOSIAL TALCOTT PARSONS - Aji Pangestu; Isa Anshori (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2024)
This study aims to describe the typology of Islamic boarding school-based madrasah and analyze the transformation process using the theory of social change with Talcott Parsons' AGIL scheme. This qualitative descriptive-analytic study was conducted at MI Al Fitrah Surabaya. Interviews, observation, and documentation were use to collect data. The results of this study revealed that; (1) The establishment of MI Al Fitrah is a form of adaptation to the response to social change in society. (2) MI Al Fitrah sets out the goals to be achieved as the fulfillment of changes that occur in society through the vision of "the realization of Islamic boarding school-based MI Al Fitrah that excels in education to produce graduates with good character, achievement, and nationalist spirit". (3) MI Al Fitrah integrates by aligning the MI AL Fitrah's curriculum and the boarding, related to moral cultivation. It is reflected in madrasa programs which are continued in pesantren activities in the form of madrasah diniyah. (4) MI Al Fitrah continues to maintain the quality of its programs to achieve the desired goals until new adaptations are needed. The maintenance is carried out as quality assurance; through evaluation.Keywords: Typology; Islamic elementary base-on boarding; AGIL Talcott Parsons’ scheme.